Substrate preference, uptake kinetics and bioenergetics in a facultatively autotrophic, thermoacidophilic crenarchaeote. Issue 5 (31st March 2016) - Urschel, Matthew R.; Hamilton, Trinity L.; Roden, Eric E.; Boyd, Eric S.
Abstract : Facultative autotrophs are abundant components of communities inhabiting geothermal springs. However, the influence of uptake kinetics and energetics on preference for substrates is not well understood in this group of organisms. Here, we report the isolation of a facultatively autotrophic crenarchaeote, strain CP80, from Cinder Pool (CP, 88.7°C, pH 4.0), Yellowstone National Park. The 16S rRNA gene sequence from CP80 is 98.8% identical to that from Thermoproteus uzonensis and is identical to the most abundant sequence identified in CP sediments. Strain CP80 reduces elemental sulfur (S8 °) and demonstrates hydrogen (H2 )-dependent autotrophic growth. H2 -dependent autotrophic activity is suppressed by amendment with formate at a concentration in the range of 20–40 μM, similar to the affinity constant determined for formate utilization. Synthesis of a cell during growth with low concentrations of formate required 0.5 μJ compared to 2.5 μJ during autotrophic growth with H2 . These results, coupled to data indicating greater C assimilation efficiency when grown with formate as compared to carbon dioxide, are consistent with preferential use of formate for energetic reasons. Collectively, these results provide new insights into the kinetic and energetic factors that influence the physiology and ecology of facultative autotrophs in high-temperature acidic environments. Abstract : Physiological, genomic and bioenergetic characterization of Thermoproteus strain CP80 provides new insights into the kinetic and energetic factors that influence the physiology and ecology of facultative autotrophs in high-temperature acidic environments. Abstract :